The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes

Traite, prostitution, inégalité - MacKinnon, Catharine A. (Collection Mobilisations, 2014)
De nos jours, il n'y a pas plus de prise de position favorable à la traite des êtres humains à des fins d'exploitation sexuelle qu'il y a de prise de position publique pour l'esclavage. Il est également très difficile de trouver des partisanes déclarées de l'inégalité… Ce n'est pourtant pas le cas de la prostitution. Certaines personnes sont pour la prostitution. Plus nombreuses sont celles qui considèrent politiquement correct de la tolérer. La plupart présument que, même si elle n'est pas réellement souhaitable, la prostitution est nécessaire, inévitable et sans dommage. Est-ce que la décriminalisation du proxénétisme et la légalisation des maisons closes assureront une plus grande sécurité physique aux personnes prostituées ? Contrairement à la Cour suprême du Canada, la juriste de réputation mondiale, Catharine A. Mac- Kinnon, répond négativement à cette question. Elle soutient que « loin de rendre la vie des prostituées plus sûre, la décriminalisation totale de la prostitution peut même la rendre encore plus dangereuse ». Pour cela, elle s'appuie sur les expériences des pays qui ont légalisé la prostitution et le proxénétisme et sur celles des pays, de plus en plus nombreux, qui décriminalisent les personnes prostituées et pénalisent les clients-prostitueurs ; la stigmatisation liée à l'activité Prostitutionnelle se retourne désormais contre ceux qui en profitent : les prostitueurs et les proxénètes.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; droits des femmes*; inégalités; justice sociale; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; travail du sexe-prostitution; violences